The feeding ecology of the redfin minnow P. burchelli, (Cyprinidae) in the Steenboks and Hex tributaries of the Breede River system - De Wet, Stefanie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.